Yield Performance of Two HYV Transplant Aman Rice under Different Nutrient Management Practices - Rajib Sarker; Newton Chandra Paul; Md. Romij Uddin; Swapan Kumar Paul (Turkish Journal of Agriculture: Food Science and Technology)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, Bangladesh to investigate the influence of plant nutrient management on the yield performance of transplant Aman rice. The experiment comprised two Aman rice varieties viz. Binadhan-15 and Binadhan-16, and ten nutrient management viz. Recommended dose of inorganic fertilizer (RDF) Urea-TSP-MoP-Gypsum-ZnSO4 @ 150-110-70-60-5 kg ha-1, Cowdung @ 10 t ha-1, Poultry manure @ 5 t ha-1, Vermicompost @ 3 t ha-1 , 25% less than RDF + cowdung @ 5 t ha-1, 50% less than RDF + cowdung @ 10 t ha-1 , 25% less than RDF + poultry manure @ 2.5 t ha-1, 50% less than RDF + poultry manure @ 5 t ha-1, 25% less than RDF + vermicompost @ 1.5 t ha-1, 50% less than RDF + vermicompost @ 3 t ha-1. The experiment was laid out in a randomized complete block design with three replications. Binadhan-15 produced taller plants (97.86 cm), effective tillers hill-1 (6.28), grains panicle-1 (101.73), higher grain (3.58 t ha-1) and straw (4.99 t ha-1) yields compared to Binadhan-16. In case of nutrient management, 50% less than RDF + poultry manure @ 5 t ha-1 produced taller plants (101.1 cm), effective tillers hill-1 (7.07), grains panicle-1 (105.1) and grain yield (4.08 t ha-1). The highest grain yield (4.25 t ha-1) was recorded in Binadhan-15 fertilized with 50% less than RDF + poultry manure @ 5 t ha-1 and the lowest grain yield (2.28 t ha-1) was obtained in Binadhan-16 fertilized with vermicompost @ 3 t ha-1. So, it can be concluded that transplant Aman rice cv. Binadhan-15 fertilized with 50% less than RDF + poultry manure @ 5 t ha-1 appears as the promising practice to obtain the highest grain yield.